2021
DOI: 10.1007/s12633-021-01271-5
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Spray of Silicon Confers Drought Tolerance in Wheat (Triticum aestivum L.) by Enhancing Morpho-Physiological and Antioxidant Potential

Abstract: Drought stress is considered one of the most severe stresses, which can result in devastating yield reduction in agriculture crops. There are many approaches recommended by the researchers and adopted by the farmers to minimize the devastating effect of drought. However, exogenous application of growth regulators in combination to plant nutrients is the innovative attitude to ameliorate the shocking effects of drought stress. So we planned a study to investigate the ameliorative effect of exogenously applied p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Additionally, it is possible to prove that a water deficit causes low plant growth. This may be attributed to physiological and biochemical disturbances that affect the regulation of stomatal opening and chlorophyll biosynthesis, which are essential for photosynthesis (Aurangzaib et al, 2021). These results corroborate those of Chen et al (2021), who found that wheat plants had a lower height when there was soil water restriction.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Additionally, it is possible to prove that a water deficit causes low plant growth. This may be attributed to physiological and biochemical disturbances that affect the regulation of stomatal opening and chlorophyll biosynthesis, which are essential for photosynthesis (Aurangzaib et al, 2021). These results corroborate those of Chen et al (2021), who found that wheat plants had a lower height when there was soil water restriction.…”
Section: Resultssupporting
confidence: 82%
“…During the reproductive stage, there is inefficient translocation of photoassimilates which affects wheat development and yield. Therefore, grain filling in plants under high water stress is restricted (Aurangzaib et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The increasing evidence during the last decade suggests the beneficial effects of Si nutrition in alleviating the damaging effects of biotic and abiotic stresses in plants [30,43]. It is well established that Si modulates the absorption of minerals, improves photosynthetic performance and regulates antioxidant systems, all of which contribute to increased tolerance against environmental stresses including drought [9,44]. However, limited literature is available on interactions of Si with essential plant nutrients like S. Some recent studies indicate that Si application enhanced the uptake of S that helped to balance the redox homeostasis in drought tolerant tomato cultivars [30].…”
Section: Shoot Npk Contentmentioning
confidence: 99%
“…Though these approaches are innovative and sophisticated, they require technical skills, huge investments and are often very time consuming. On the other hand, the use of shot-gun, inexpensive approaches such as seed priming and the foliar application of plant growth regulators and mineral nutrients has become increasingly popular in the recent past [9,10]. Seed priming is an effective agro-technical approach that minimizes the risk of poor germination and impaired seedling establishment under harsh conditions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Jeyazsri et al (2021) indicated grain lling stage in cereals as one of the most sensitive growth stage under drought stress. Different studies on wheat and the other crops have shown that during grain lling stage of plant water scarcity signi cantly affects the grain weight due to early senescence [12,13]. The stress response can also vary depending on the developmental stage during which a plant is subjected to stress [14,15].…”
Section: Introductionmentioning
confidence: 99%